Ciclo de vida organizacional e mensuração de desempenho: uma percepção no uso de medidas de desempenho em empresas industriais da Paraíba - Santana Junior, Gilvan Medeiros de (2017)
The present research contributes with the advancement of the Organizational Life Cycle (CVO) literature and the Performance Measurement, due to the absence of national studies involving CVO and performance measures. Thus, the objective of this study was to analyze the influence of life stages on the use of performance measures. To do so, the model of Lester, Parnell and Carraher (2003) was used to identify the stages of the life cycle that were the companies participating in the research. And the performance measures presented in the study by Callado, Callado and Almeida (2007) were adapted to measure the level of intensity of use of the measures. The research sample was carried out by 50 industrial companies registered in the Federation of Industries of the State of Paraíba - FIEP / PB. From the use of the discriminant analysis it was possible to classify the companies in the respective stages of life and, through the multivariate regression analysis, the influence of the stages of life in the use of performance measures was analyzed. The results showed that, although companies were identified in the different stages of life, the stage associated with the birth was the one that presented the largest number of companies. With regard to the use of performance measures, there was a strong use in measures related to business revenue and the level of product quality. There was also a negative correlation between the birth phase and the use of performance measures (financial and non-financial). And a positive correlation between the rejuvenation stage and the use of both measures of performance, however, this correlation was higher with the use of financial measures to the detriment of non-financial measures. Regarding the influence, the results showed that the stages of growth, maturity and rejuvenation influence the intensity of use of financial measures and that the stages of birth and rejuvenation influence non-financial measures, however, the influence of birth is negative. Therefore, it is concluded that companies use less performance measures (financial and non-financial), in cases where they present characteristics of the life cycle stage, contradicting part of the literature that states that in the early stages of life companies give preference to the use of non-financial performance measures.